Dependence of Reallocated Sectors Count on HDD Power-on Time - N. Nasyrov, Iskandar; I. Nasyrov, Ildar; I. Nasyrov, Rustam; A. Khairullin, Bulat (International Journal of Engineering and Technology, 2018)
The problem of SMART-data ambiguity in different models of hard disk drives of the same manufacturers is considered. This circumstance creates obstacles for the use of SMART technology when assessing and predicting the reliability of storage devices. The scientific task of the work is to study the dependence of the hard disk failure probability on the reliability parameters values for each individual storage device of any model of any manufacturer. In the course of the study, two interrelated parameters were analyzed: â€œ5 Reallocated sectors countâ€ and â€œ9 Power-on hoursâ€ (the number of hours spent in the on state). As a result of the analysis, two types of dependences were revealed: drooping and dome shaped. The first means the maximum failure frequency of information storage devices immediately after commissioning, the second - after a certain period of time, actually coinciding with the warranty period for the products (two years). With the help of clustering in plane according to the coordinates of the number of reallocated sectors and the time of operation, two different reasons for the failure of the drives were discovered: due to deterioration of the disk surface and due to errors in the positioning of the read / write heads. Based on the variety of types of causes and consequences of equipment failure, the task of individual assessment of an individual data storage device reliability is proposed to be solved using several parameters simultaneously.Â Â